Determination of tensile characteristics and design of eco-efficient UHPC. (August 2021) - Isa, M.N.; Pilakoutas, Kypros; Guadagnini, Maurizio
Highlights: Flexural behaviour, Energy absorption and fracture energy of E-UHPC. Fracture energy-based approach to address mesh sensitivity of smeared crack models. A precise tensile stress–strain relationship for E-UHPC is obtained. The suitability of MC10 constitutive model is assessed for use in UHPCs. A simple constitutive model to predict the tensile behaviour of E-UHPC is proposed. Abstract: Eco-efficient Ultra-High Performance Concrete (E-UHPC) containing Recycled Steel Fibres has been recently developed to reduce the cost and environmental impact of UHPC in the construction industry. Nevertheless, currently there are no design guidelines for high-performance fibre reinforced materials with hardening post-crack tensile characteristics, such as UHPC. The determination of the post-crack tensile characteristics of UHPC is also a major challenge experimentally and numerically. In this paper, the notched three-point bending test is used in conjunction with Finite Element (FE) inverse analysis to characterise the tensile properties of E-UHPC. To address issues of spurious mesh dependency in smeared crack FE models, the post crack tensile properties are determined using a fracture energy approach. A mesh independent solution is developed by using a characteristic length scaling procedure as a function of finite element size. Based on that, a simple and precise model for predicting the constitutive tensile stress strain ( σ - ε ) law of UHPC using simple strength and mix parameters (compressive strength, flexural strength, fracture energy, fibre dosage and recycle steel fibre content) is developed. This model is then used to derive E-UHPC specific design guidelines in line with current fib Model Code design provisions.